The Saccharification of Hazelnut Husks to Produce Bioethanol - (:unkn) unknown (TAYLOR & FRANCIS INC, 2015)
Biofuels have been produced industrially by fermentation of sugars derived from wheat, corn, sugar beets, sugar cane, and molasses. But because of economic and environmental issues an efficient substrate must be used for bioethanol production. Hazelnut husk, a renewable and low-cost natural recourse, is not used industrially. The objective of this study was to examine the saccharification of hazelnut husk for the production of fermentable sugars. Hazelnut husks were treated with sulphuric acid for varying periods (30-90 min), with varying acid concentrations (1-5%, w/w) and sample concentrations (1/5, 1/10, 1/15, 1/20 solid/liquid ratio). The maximum sugar yield of 18.63 +/- 0.51% was obtained with 90 min incubation time, 4% acid concentration, and 1/20 sample concentration. The sugar composition of the acid hydrolyzed hazelnut husks was analyzed using thin layer chromatography. Arabinose, glucose, mannose, and xylose were found to be present. Fermentability of the hyrolysate was also tested.
Keywords: acid hydrolysis; agricultural residues; bioethanol; biomass; fermentation; hazelnut husk; DILUTE-ACID HYDROLYSIS; ETHANOL-PRODUCTION; CORN STOVER; WHEAT-STRAW; PRETREATMENT; HEMICELLULOSE; FERMENTATION; OPTIMIZATION; BIOMASS